Learning with Social Media - Dueñas, Daniel (CIEX JOURNAL, 2023)
“Learning with Social Media” is a workshop proposal based on research carried out at CIEX (Centro de Idiomas Extranjeros “Ignacio Manuel Altamirano”) entitled “USING SOCIAL NETWORKS FOR PROMOTING AUTONOMOUS LEARNING IN BASIC ENGLISH STUDENTS AT CIEX”. The objective of this workshop is to present new alternatives for online language teaching, including some examples of activities based on Twitter, one of the most popular social networks at the moment. During the workshop, the audience will be involved in the activities using their smartphones and Twitter, additionally, they will be able to explore the use of social media with educational purposes.